General outlook of the elaboration of nitrogen doped graphenic materials from the reaction between an amino alcohol and metallic sodium. (January 2023) - Moumaneix, L.; Fontana, S.; Lapicque, F.; Hérold, C.
Abstract: Nitrogen-doped graphenic materials (N-Gr) are attracting increasing interest in the field of electrocatalysis, where their applications as noble metal-free catalysts or as catalyst supports are explored worldwide. Solvothermal-based processes are an efficient way to produce large quantities of N-Gr, without compromising their valuable properties. Reported in earlier publications, our elaboration route is based on a solvothermal reaction between various organic alcohols, e.g. cyclohexanol, ethanolamine, 1-(2-hydroxyethyl)piperidine, and metallic sodium, followed by a pyrolysis treatment under nitrogen flow. Rarely investigated in the literature mainly due to their complex mechanisms, the understanding of such processes opens many paths to tailor the properties of N-Gr, leading to high porosity (>2200 m 2 /g), good crystallinity, high purity, etc. The present article focuses on the influence of the solvothermal reaction experimental parameters on the final N-Gr, i.e. temperature, pressure, and sodium content. The elaborated materials are studied through multi-scale and complementary characterization techniques, i.e. Raman spectroscopy, thermogravimetric analysis, X-ray photoelectron spectroscopy, N2 adsorption at 77 K. An overview of the whole process follows the experimental part, giving quick access to optimized experimental parameters depending on the desired N-Gr properties, e.g. yield, crystallinity or porosity. By way of illustration, some trends were evidenced, such as (i) the larger conversion rate of solvent into crystalline carbon material as the reaction temperature is increased (300–380 °C), (ii) the increase of the surface area and the larger nitrogen content with increasing pressure (100–200 bar), and (iii) the beneficial impact of the sodium content on the yield and the material crystallinity (Na/solvent ratio 1–2). Graphical abstract: Highlights: We aimed at the preparation of nitrogen doped graphenic materials from the reaction between an amino alcohol and sodium. We focused on the influence of the solvothermal reaction experimental parameters on the final N-Gr. Larger conversion rate of solvent into crystalline carbon material was observed when the reaction temperature is increased. The surface area and nitrogen content increased with pressure. As the amount of sodium increases, the yield of the reaction increases.